Useful functional recovery and quality of life after surgical treatment of peroneal nerve injuries - Rasulić, Lukas; Nikolić, Živan; Lepić, Milan; Savić, Andrija; Vitošević, Filip; Novaković, Nenad; Radojević, Stefan; Mićić, Aleksa; Lepić, Sanja; Mandić-Rajčević, Stefan (Frontiers in Surgery, 2022)
Injuries to the peroneal nerve recover spontaneously in about a third of patients, but in the remaining 2/3 a surgery may be needed. The recovery after surgery is not always satisfactory and the patients may need an orthosis or a walking-aid to cope with regular daily activities. This study evaluates the useful functional recovery and QoL in surgically treated patients with peroneal nerve (PN) injuries. The study involved 51 patients who have undergone surgical treatment due to peroneal nerve injury in our department, within a 15-year period (2006-2020). Thirty patients (59%) were treated with neurolysis, 12 (23%) with nerve repair techniques and 9 (18%) with tendon transfer. Neurolysis is employed in the least extensive nerve injuries, when nerve continuity is preserved and yields a motor recovery ratio nearing 80%. Nerve repairs were followed by 58,33% of patients achieving M3+ recovery, while 41,66% recovered to the useful functional state (M4 or M5) With the use of tendon transfers, all patients recovered to the M3+, while 66,7% recovered to M4. All our results correspond to the results of previous studies. No statistically significant differences were found regarding the QoL of the groups. There is an apparent advantage of neurolysis, over nerve repair, over tendon transfer procedure, both in terms of useful functional recovery, and foot-drop related QoL. However, when involving all aspects of QoL, these advantages diminish. Individual approach leads to the optimal results in all groups of patients.